Análisis de criterios y métodos de valuación usados para activos intangibles de origen intelectual. (2014)
Intangible assets are now constitutes an element that generates a strong impact on the effectiveness and efficiency of organizations. For this reason, it is crucial to have a proper understanding of the term along with its components to be included in the accounting. In this sense, we found that many companies just ignore the importance of these assets, not contemplate in their balance sheets, given the presence of ambivalences at the time of measurement; whenever having the character of intangible difficulties of this task. Therefore, as alternative fair value as the valuation method for intangible assets are given the importance they deserve and can be valued and integrated into corporate accounting. This, considering the existing drawbacks when classifying intangible assets specifically intellectual origin.